The Temperature Dependence of Gravitation for the Metallic Balls - Measured with a Torsion Balance Scale (Global Journal of Science Frontier Research, 2017)
We use a torsion balance scale to measure the attraction between two large lead balls and two smaller brass balls, connected with an up-side down T bar that is hung with a string. The vertical part of the T bar is attached with a mirror that reflects a laser beam to provide a light spot that shows how much the T bar has turned. It is observed that the gravitational forces between the lead balls and the brass balls are reduced when the temperature of the lead balls increased. Thus, this experiment shows clearly the existence of a repulsive gravitational force that increases as the temperature of the lead balls increase. This supports that the charge-mass interaction is the reason that the theories of Galileo, Newton, and Einstein failed to explain the Anomaly of the Space-Probes and flybys, and the fact that not all the neutral subjects necessarily fall with the same acceleration. In other words, the Newtonian law of gravitation is only approximately valid. Thus, the attempts such as J. Luo (罗俊)'s to obtain an accurate gravitational coupling constant with just improved skill are futile. The physical picture of Galileo, Newton, and Einstein on gravitation needs to be improved.
Keywords: repulsive gravitation; invalidity of E = mc2